If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 7(4) = 9 Multiply 7 * 4 Y + 28 = 9 Reorder the terms: 28 + Y = 9 Solving 28 + Y = 9 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + Y = 9 + -28 Combine like terms: 28 + -28 = 0 0 + Y = 9 + -28 Y = 9 + -28 Combine like terms: 9 + -28 = -19 Y = -19 Simplifying Y = -19
| 25x=36x | | y^3-5y+6=0 | | 4a+7-a=19-a | | 2x-5y-xy= | | lx+3l+8=2 | | -17=2n-3 | | -6(4x+1)+7x+9(x-4)=4 | | 4x^2-13x=-8 | | 5x^2+23x-35=0 | | 9x+14y=221 | | x=5y+16 | | -4n-8=10n-2 | | Cos(4x)=cos(3x) | | -273+240= | | x+1/5+2-x/3=1/15x | | 24a-22=14(1-6a) | | 53+25+2=180 | | 10sin^24x=5 | | 3(m-n)+5n-7m= | | 10p+9-11p=-3k-39 | | 3x+75=4x-(34-2x) | | 107+x=180 | | 6bp= | | 6-bp= | | 6(b-p)= | | -4x-(-13)=30 | | 7=5-2d | | g-4= | | 2x-3(x+1)=3 | | -5+10n=15 | | X+100=y | | 2x-47=-3 |